HUSEIN MUHAMMAD'S PROGRESSIVE THINKING ABOUT FEMALE JURISPRUDENCE; A Descriptive Analyctical Study - Septi Gumiandari; Ilman Nafi’a (IAIN Syekh Nurjati Cirebon, 2019)
This study aims to describe the conversation, debate and new interpretations of progressive thinking of Husein Muhammad for the sake of reforming the rules of Islamic law with gender equality perspective. This research uses a qualitative methodology with a descriptive approach. The results showed that Husein Muhammad is a male Muslim feminist. In contrast to most other Islamic feminists who deconstruct religious texts and look for possible reconstructions in the values of secular humanism, Husein's ideas have their own distinctiveness, because in addition he has a depth of classical Islamic literature in analyzing or competing arguments against gender inequality in society, he also carried out reconstruction by finding references contained in the classical Islamic treasures which he considered more in line with the spirit of Koran’s justice. This is what makes Husein's ideas in defending women considered by some as the only capable and important in Indonesia to be maintained. Some of the methodologies used are the Contextual Interpretation methodology, Maqashid al-Shari'ah, Asbab al Nuzul, Special Text and General Text, Understanding Causality and Social Reality, and Ta'wil. Some of these methodologies are important because they are able to provide understanding to Islamic attackers without having to be apologetic, as many contemporary scholars show.